ChemInform Abstract: Design, Functionalization Strategies and Biomedical Applications of Targeted Biodegradable/Biocompatible Polymer‐Based Nanocarriers for Drug Delivery. Issue 23 (16th May 2013) - Nicolas, Julien; Mura, Simona; Brambilla, Davide; Mackiewicz, Nicolas; Couvreur, Patrick
Abstract Review: 446 refs.